Villa Borg - Archäologiepark Römische Villa Borg (2001)
[Dt.:] Die Villa Borg ist der Nachbau einer römischen Villenanlage mit Baderäumen, Wohn- und Wirtschaftstrakt, die in Borg (Gem. Perl) durch Ausgrabungen erschlossen wurde. Die Website bietet bebilderte Berichte zu den Grabungen und naturwissenschaftlichen Begleituntersuchungen mit Plänen und Fotos. Außerdem gibt es ein umfangreiches Programm für Besucher. - [Engl.:] The Roman villa is the true to scale reconstruction of a villa rustica with place for bathing, residence buildings and economical section, which has been detected and excavated in Borg, Germany. The website gives illustrated reports about the fieldwok results and the scientific methods with plans and pictures. Further there is a program with events for visitors of the museum.